Optimization of PV-Wind-Hydro-Diesel hybrid system by minimizing excess capacity - Ab. Razak J.; Sopian K.; Ali Y.; Alghoul M.A.; Zaharim A.; Ahmad I. (EuroJournals, Inc., 2023)
Optimization of renewable energy hybrid system looks into the process of selecting the best components and its sizing with appropriate operation strategy to provide cheap efficient, reliable and cost effective. The techno-economic analysis usually looks at the cheapest cost of energy produced by of system components while neglecting the excess capacity of the combination. This paper discusses the optimization of the hybrid system in context of minimizing the excess energy and cost of energy. The hybrid of pico hydro, solar, wind and generator and battery as back-up is the basis of assessment. The system configuration of the hybrid is derived based on a theoretical domestic load at a remote location and local solar radiation, wind and water flow rate data. Three demand loads are used in the simulation using HOMER to find the optimum combination and sizing of components. Another set of demand loads is used to investigate the effect of reducing the demand load against the dominant power provider of the system. The results show that the cost of energy can be reduced to about 50% if the demand load is increased to the maximum capacity. Reducing the load to the capacity of the dominant power provider will reduce the cost of energy by 90%. EuroJournals Publishing, Inc. 2009.